Gender differences in the quantitative and qualitative assessment of chronic pain among older people - Grażyna Puto; Iwona Repka; Agnieszka Gniadek (Frontiers Media S.A., 2024)
BackgroundPain, regardless of its causes, is a subjective and multidimensional experience that consists of sensory, emotional and cognitive factors that cannot be adequately captured by a single number on a pain scale. The aim of the study was to understand gender differences in the assessment of quantitative and qualitative chronic pain among older people.MethodsThe study used a questionnaire that included questions about demographic and social characteristics as well as the following scales: Abbreviated Mental Score (AMTS), Personal Activities of Daily Living (PADL) by Katz, Instrumental Activities of Daily Living (IADL) by Lawton, Geriatric Depression Scale (GDS-15), McGill Pain Questionnaire (MPQ).ResultsThe pain rating index based on rank values of adjectives was higher among women than men (18.36 ± 7.81 vs. 17.17 ± 9.69, p = 0.04). The analysis of the frequency of selection of individual adjectives describing the sensory aspects of pain showed that men described the pain as "stabbing" more often than women (26.1% vs. 14.3%, p < 0.05). Women chose adjectives from the emotional category more often than men (59.8% vs. 75.4%, p < 0.05), describing the pain as "disgusting" (8.9% vs. 1.4%, p < 0.05), "unbearable" (19.6 vs. 4.3, p < 0.05). In the subjective category, there was a difference between women and men in terms of describing pain as "terrible" (23.2% vs. 7.2%, p < 0.05) and as "unpleasant" (11.6% vs. 23.3%, p < 0 0.05).ConclusionWhen referring to pain, women tend to employ more detailed and factual language, indicative of heightened emotional sensitivity. Men tend to use fewer words and focus on the sensory aspects of pain. Subjective aspects of pain were demonstrated by both women and men.